Struggling with entrepreneurial ecosystems - Michael Fritsch (Friedrich Schiller University Jena, Faculty of Economics and Business Administration, 2024)
This article discusses the concept of entrepreneurial ecosystems. In particular, three propositions are made for further development of the concept. First, it is argued that entrepreneurial ecosystems should be regarded a part of the regional innovation system. Second, the scope of the concept should be expanded beyond high-performance start-ups and their founders to include the entire universe of 'everyday' entrepreneurship. Third, the concept should account for the incumbent firms and the regional workforce. The paper then outlines main challenges of further development of the concept.
Keywords: L26; R11; O2; 330; Regional entrepreneurship; entrepreneurial ecosystems; regional development; entrepreneurship policy